Voices from the Frontlines:Teachers' Perceptions of High-Stakes Testing - Jones, Brett D.; Egley, Robert J. (Education Policy Analysis Archives, 2004)
The purpose of this study was to investigate whether teachers perceived Florida’s high-stakes testing program to be taking public schools in the right direction. More importantly, we sought to understand why teachers perceived the tests to be taking schools in the right or wrong direction. Based on the survey results of 708 teachers, we categorized their concerns and praises of high-stakes testing into ten themes. Most of the teachers believed that the testing program was not taking schools in the right direction. They commented that the test was used improperly and that the one-time test scores were not an accurate assessment of students’ learning and development. In addition, they cited negative effects on the curriculum, teaching and learning, and student and teacher motivation. The positive effects cited were much fewer in number and included the fact that the testing held students, educators, and parents accountable for their actions. Interestingly, teachers were not opposed to accountability, but rather, opposed the manner in which it was currently implemented. Only by understanding these positive and negative effects of the testing program can policymakers hope to improve upon it. To this end, we discuss several implications of these findings, including: limiting the use of test scores, changing the school grading criteria, using alternative assessments, modifying the curriculum, and taking steps to reduce teaching to the test.